Experiential Learning Strategy-Based Group Counseling to Improve Self-Efficacy (Jurnal Bimbingan Konseling, 2019)
This study aimed to know the effectiveness of experiential learning strategy-based group counseling to improve the self-efficacy of the Tenth Grade students of Senior High School (SMA). This study used pre-test – post-test one group design by involving seven students as the sample to form a group chosen by using purposive sampling. For more, treatments for the group were done in the five times session through experiential learning strategy-based group counseling. The collected data from these treatments were analyzed by using Wilcoxson analysis. From the analysis, it was known that the experiential learning strategy-based group counseling was effective to improve self-efficacy (z = -2.366, p = < 0.05). These findings prove that experiential learning strategy-based group counseling is effective to improve students’ self-efficacy.